Immunoglobulin G4-related inflammatory pseudotumor of the right ventricle with right coronary artery occlusion. Issue 4 (October 2022) - Shibasaki, Ikuko; Nakajima, Takahiro; Matsuoka, Taiki; Kanno, Yasuyuki; Kanazawa, Yuta; Takei, Yusuke; Tuchiya, Go; Saito, Shunsuke; Konishi, Taisuke; Sakuma, Masashi; Toyoda, Shigeru; Fukuda, Hirotsugu
Abstract: Immunoglobulin G4-related inflammatory pseudotumors are usually benign. Such tumors of cardiac origin are extremely rare, with no primary cardiac tumors reported to date. We report a case of a 77-year-old woman, with a medical history of diabetes, hypertension, and hyperlipidemia, who was diagnosed with a malignant cardiac tumor on preoperative imaging and had a confirmed pathological diagnosis of immunoglobulin G4-related inflammatory pseudotumor. She was examined for atherosclerosis obliterans, and coronary computed tomography revealed obstruction of the right coronary artery and a cardiac tumor in the right atrium. A suspected malignant tumor measuring 40 mm (maximum standardized uptake value: 12.2) bordering the right atrium was detected using 18F-fluorodeoxyglucose positron emission tomography. Her tumor was in contact with the heart, making biopsy impossible. She was diagnosed with malignancy on preoperative imaging and underwent tumor resection, tricuspid valve replacement, right atrial and right ventricular plasty, coronary artery bypass, lung resection, and diaphragmatic repair. However, the final pathological diagnosis was immunoglobulin G4-related inflammatory pseudotumor. Preoperative diagnosis of immunoglobulin G4-related inflammatory pseudotumor is extremely difficult; however, if the condition is diagnosed preoperatively, chemotherapy or steroid therapy should be administered, and patients who do not respond to chemotherapy should be considered for surgical treatment. Learning objective: Immunoglobulin G4-associated inflammatory pseudotumor is extremely rare. Preoperative imaging diagnosis of immunoglobulin G4-associated inflammatory pseudotumor is extremely difficult, and pathology with biopsy is the only definitive diagnosis. However, if we could make an accurate preoperative diagnosis, patients should be treated with chemotherapy or steroids, and surgical treatment should be considered for patients who do not respond to chemotherapy or steroids.